A CONTRASTIVE STUDY DRAMA THEATRE IN ENGLISH AND UZBEK LANGUAGES (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
Drama theatre represents one of the most influential artistic systems in world culture. English and Uzbek drama theatres, despite belonging to different civilizational traditions, share core structural features such as conflict, dialogue, and actor-centered expression. English drama evolved from medieval religious plays towards the Renaissance golden age and modernist experimentation, while Uzbek drama emerged from folk performance traditions and the reformist Jadid movement.